Charged snowball in nonpolar liquid - Chikina, I.; Shikin, V.; Varlamov, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The problem of correct definition of the charge carrier effective mass in superfluid helium is revised. It is demonstrated that the effective mass M of a such quasiparticle can be introduced without use of the Atkins’s idea concerning the solidification of liquid He in the close vicinity of ion. The two-liquid scenario of the «snowball» mass formation is investigated. The normal fluid contribution to the total snowball effective mass, the physical reasons of its singularity and the way of corresponding regularization procedure are discussed. Within of two-liquid model the existence of two different effective snowball radiuses: Rid for superfluid flow component and Rn for the normal one, Rn > Rid is demonstrated. Agreement of the theory with the available experimental data is found.